UltraLab – free software for conducting psychology experiments - Filipović Đurđević, Dušica; Đurđević, Đorđe (Primenjena psihologija)
The main goal of this paper is to present a new tool for preparing and conducting the psychological experiments which we created to enrich and facilitate the education process within the practicals in the area of cognitive psychology and related fields. It has been designed as an aid in the teaching process at the university level, but due to its simplicity it can easily be applied at earlier levels of schooling as well. We described a computer program UltraLab which created with an idea to follow contemporary trends and be a software which is free, very simple to use in preparing and conducting the experiments, and yet flexible - it can cover a wide range of experimental paradigms. A download link is provided as well. In this paper we describe the basic technical features, give detailed instructions for the preparation of experimental files, as well as for reading the data files. Finally, we point out the advantages which the application of this tool brings to the students who are acquiring the knowledge of experimental psychology.